(untitled) (Advances in Applied Biological Research, 2025)
Chronic kidney disease (CKD) affects 10–15% of adults globally and is often underdiagnosed due to limitations in standard serum creatinine assessments. This case report presents a 56-year-old male with a 1.5-year history of CKD and 5 years of hypertension, treated at Jeena Sikho Lifecare Limited Hospital, Derabassi, with a comprehensive Ayurvedic regimen including medicines and Panchakarma therapies. The patient showed marked improvement in multiple clinical parameters: pedal oedema decreased from grade 4˚ to 1˚, pain resolved completely (3/10 to 0/10), sleep quality improved from 3/10 to 7/10, and itching, initially rated 6/10, was fully alleviated. Vital signs stabilized, with blood pressure maintained at 120/80 mmHg, and body weight reduced from 82 kg to 73 kg, reflecting positive effects of lifestyle and dietary modifications. Laboratory investigations demonstrated gradual improvement and stabilization, with haemoglobin ranging from 7.1 to 9.3 gm/dL, urea decreasing from 200.85 mg/dL to 66.5 mg/dL, creatinine improving from 7.25 mg/dL to 5.61 mg/dL, and uric acid declining from 9.87 mg/dL to 6.87 mg/dL. Overall, the patient achieved normalization of clinical and laboratory parameters, highlighting the potential of Ayurveda as a safe, cost-effective, and integrative approach for managing CKD, particularly for patients seeking holistic healthcare solutions.